Strategi Pengembangan Usaha Kain Tenun Dan Tapis Di Desa Talang Jawa Kecamatan Pulau Panggung Kabupaten Tanggamus - Sandova, Dea; Gunarto, Toto (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The woven fabric and tapis business in Talang Jawa Village is a superior business that has received government attention but is currently experiencing a decline. The purpose of this study is to find out how the right business development strategy in the woven fabric and tapis business in Talang Jawa Village is expected to increase business competitiveness. This study uses a SWOT Analysis tool which consists of 5 stages, namely identifying internal factors and external factors, creating a SWOT Matrix, analyzing the IFAS Matrix and EFAS Matrix, analyzing the Internal-External Matrix and creating a SWOT Quadrant. This questionnaire was filled in by 15 selected expert respondents. The results of this study indicate that the right strategies to use are 1) Marketing woven fabric and tapis business products on platforms, websites, and other social media so that this business can quickly develop and be known by the wider community, and maximize existing facilities and infrastructure. 2) Conduct collaboration programs with the fashion and interior design industries so as to position weaving and tapis as premium materials in the fashion industry and contemporary interior design. 3) Conduct partnerships with tourism agencies or industries to become a creative and educational tourist attraction so that this business can develop an artisan center or workshop that is open to tourists.